Demokrasi dan Transformasi Digital : Analisis Digitalisasi Politik Melalui Penerapan E-Voting dalam Meningkatkan Mutu Demokrasi - Sadam, Muhammad; Araafi, Faathur Al; Arafah, Yusran (Politika: Jurnal Ilmu Politik, 2024)
In the rapidly evolving digital era, many democracies are undertaking digital transformation through the implementation of e-voting. E-voting is a digital system that aims to be a transformation tool in the voting mechanism, this will make changes in the election method that was previously carried out conventionally to digitalization. In conducting the research, the author adopts a qualitative approach through a literature study to explore the relationship between democracy and digital transformation through the implementation of e-voting. The application of e-voting in the electoral system can provide several advantages in increasing efficiency, participation, and transparency. However, there are several challenges that need to be observed related to the implementation of e-voting, where the security aspect is an issue that needs to be considered. The vulnerability of e-voting systems can be an important discourse to prevent cyber-attacks and vote manipulation that can reduce the integrity of democracy. Therefore, e-voting systems need to be equipped with good security procedures to protect voters from data manipulation through various cyber-attacks. Thus, the presence of an e-voting system can be an effective tool in improving the quality of democracy, although it has some security issues that need to be considered.   Keywords: Democracy, Transformation, Digital, E-voting